SURFACE ELECTRONIC-STRUCTURE OF THE SRSN1-XSBXO3 PEROVSKITE SYSTEM - Roberts, A; Flavell, W; Hoad, D; Egdell, R; Randall, S; Wincott, P; Teehan, D (1994)
Pure and antimony-doped strontium stannate (SrSn1-xSbxO3) samples have been prepared by a high temperature (1360 °C) solid-state synthetic procedure over the composition range 0≤x≤0.40. The bulk properties have been determined by powder X-ray diffraction (XRD), energy dispersive X-ray analysis (EDAX) and scanning electron microscopy (SEM), showing the SrSn1-xSbxO3 system to be single phase over the doping range 0≤x≤0.085. Surface analysis of SrSn1-xSbxO3 ceramic discs by X-ray photoemission (XPS), Auger electron spectroscopy (AES) and synchrotron excited valence band photoemission has probed the occupied electronic states, whilst the unoccupied states have been investigated by inverse photoemission spectroscopy (IPES). Considerable segregation of the Sb-dopant to the surface of the sample has been demonstrated. We show that this system exhibits strong similarities to the well studied Sb-doped SnO2 system and the less well characterized Sb-doped BaSnO3 perovskite.